The Influence of Strategic Planning and Digital Leadership on Organizational Performance in the Digital Era (Case Study: Sumenep Communications and Information Service) - Qorisyatul Arika; Uswatun Hasanah; Nurita Andriani (Majapahit Journal of Islamic Finance and Management, 2026)
Digital transformation has become a strategic necessity in improving the quality of governance. This study aims to analyze the influence of Strategic Planning and Digital Leadership on Organizational Performance at the Sumenep Regency Communication and Information Service. The type of research used is quantitative with an associative approach. The population in this study were all 60 employees of the Sumenep Communication and Information Service, who were also used as samples. Primary data were collected through questionnaires and Data analysis tests consist of Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test and T Test (partial test), F Test (simultaneous test) and Determination Coefficient Test (R2). The analysis technique in this research uses the Multiple Linear Regression Test. The results of the study indicate that (1) Strategic Planning has a positive and significant effect on Organizational Performance; (2) Digital Leadership has a positive and significant effect on Organizational Performance; and (3) Strategic Planning and Digital Leadership simultaneously have a significant effect on Organizational Performance. The coefficient of determination shows that both independent variables contribute 67.9% to Organizational Performance, while the rest is influenced by other factors outside this study. These findings confirm that the success of local government digital transformation is highly dependent on careful planning and effective digital leadership.